2009
DOI: 10.1159/000211717
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Fluoride Concentrations and pH of Dentifrices on Plaque and Nail Fluoride Levels in Young Children

Abstract: To evaluate the influence of dentifrice pH and fluoride (F) concentration on F uptake by plaque and nails, two sets of 5- to 6-year-old children were randomly allocated into four groups, according to the type of dentifrice they had been using for 1 year: (1) experimental liquid dentifrice (ELD), 1,100 ppm F, pH 7.0; (2) ELD, 1,100 ppm F, pH 4.5; (3) ELD, 550 ppm F, pH 4.5, and (4) commercial toothpaste, 1,100 ppm F, pH 7.0. In one set of children, nails were clipped. In the second, plaque samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
5
26
1
2
Order By: Relevance
“…All dentifrices presented NaF as F compound with silica as abrasive. The composition of the liquid dentifrices is in accordance with a previous study . The liquid dentifrices have the consistency of a gel, but with more fluidity.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…All dentifrices presented NaF as F compound with silica as abrasive. The composition of the liquid dentifrices is in accordance with a previous study . The liquid dentifrices have the consistency of a gel, but with more fluidity.…”
Section: Methodssupporting
confidence: 86%
“…On the other hand, the reduction of the pH and change of consistency (from paste to liquid or gel) has been shown to be effective in increasing plaque fluoride uptake in vivo . Acidic dentifrices with 550 ppm F have the same effectiveness as neutral 1100 ppm F dentifrices in reducing enamel demineralization in vitro and caries progression in vivo …”
Section: Introductionmentioning
confidence: 99%
“…Low-fluoride (500 ppm) acidic (pH 4.5 or 5.5) NaF dentifrices have been shown in pH-cycling studies to be as effective as 1,100 ppm F neutral NaF dentifrices. This was confirmed in clinical studies showing that a 550 ppm F pH 4.5 dentifrice led to similar plaque fluoride concentrations as the 1,100 ppm F pH 7.0 dentifrice 12 and that both dentifrices led to similar caries increments in a 20-month clinical trial with 4-5-year-old children (unpublished date).…”
Section: Results and Literature Reviewmentioning
confidence: 54%
“…Since dental caries has become a polarized disease and conventional fluoride therapy seems to have little effect for highrisk groups [Pessan et al, 2008], alternatives have been proposed to increase the effectiveness of fluoridated vehicles Buzalaf et al, 2009;Takeshita et al, 2009;Vilhena et al, 2010;Amaral et al, 2013]. All fluoride varnishes tested in the present study were shown to significantly increase remineralization of enamel carious lesions, following a dose-response relationship.…”
Section: Discussionmentioning
confidence: 65%